Adjustment and Psychological Evolution in Patients with Acute Coronary Syndrome after Participation in a Cardiac Rehabilitation Program - León-Zarceño, Eva; Boix, Salvador; Arrarte, Vicente; Cantón, Enrique; Ángel Serrano-Rosa, Miguel (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
The psychological variables have a special relevance in the coronary affectations. The aim of the present work was to study the evolution of different psychological variables, of quality of life and of adjustment psychosocial, in patients who have suffered an acute coronary syndrome (ACS) and attended a cardiac rehabilitation program, which included, among other, a module of physical activity. The measurements were made when the ACS debuted and 3 months after the cardiac event in a total of 146 men (57.86 years of age (dt = 9.45)) who had undergone a diagnostic catheterization with therapeutic intent within 3 days. The study design was of the quasi-experimental, prospective and longitudinal type. The results at 3 months after suffering the cardiac event show lower levels of anxiety (Cohen’s d = .61; p < .01), depression (Cohen’s d = .33; p < .05), psychological distress (Cohen’s d =. 72; p < .01) and anger (Cohen’s d = .34; p < .01), and higher personal strength scores (Cohen’s d = .37; p < .01) or life appreciation (Cohen’s d =. 35, p < .01). In the ACS, knowing the psychosocial evolution of the patient is considered fundamental next to the usual medical control.